Eksaminasi Putusan Klausul Non-Kompetisi Berdasarkan Teori Keadilan: Studi Putusan NO. 459/PDT/2019/PT.BDG - Muhammad Bisri Affandi; Muhammad Fajar Aulia Fachrendy; Muhammad Raja Mulia Darmawan Kasau; Muhammad Nadhiel Hibatullah (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2024)
Non-Competition Clauses are created with the aim of ensuring that a company's secrets are maintained by creating an agreement between the company and employees. This clause is included in the employment agreement so that workers who agree to the agreement are not permitted to work in another company in the same field within the specified time limit starting after termination of employment, which makes this clause raise to many pros and cons. However, until now there is no Indonesian positive law that explicitly regulates the Non-Competition Clause, so as long as both parties agree, the Non-Competition Clause will apply, provided that the implementation of the Non-Competition Clause must be in accordance with the legal conditions of the agreement as regulated in Article 1320 of Burgerlijk Wetboek and comply with Article 1338 of the Burgerlijk Wetboek which states that all agreements made legally are valid as law for those who make them. This research uses a doctrinal legal methodology which will analyze Decision No.459/PDT/2019/PT.BDG and relate it to John Rawls's Theory of Justice. The conclusion of this writing is that the results of the appeal decision number 459/PDT/2019/PT.BDG are in line with John Rawls' Theory of Justice.